Domestic entities and access and benefit‐sharing: A legal critique of Divya Pharmacy v Union of India. Issue 3 (16th July 2022) - Jolly, Stellina
Abstract: In the case of Divya Pharmacy v Union of India, the Uttarakhand High Court in India provided an innovative interpretation of the concept of access and benefit‐sharing by ruling that an Indian company, having no foreign participation, is mandated to undertake fair and equitable benefit‐sharing under the Biological Diversity Act 2002, India. The court employed a purposive interpretation, relying on the provisions of the Convention on Biological Diversity and its Nagoya Protocol. This article critically explores the Divya Pharmacy judgement, arguing that where a domestic statute makes a specific exemption in favour of domestic entities articulating a clear legislative intention, the judiciary should have engaged with constitutional provisions and environmental principles, which are part of domestic laws rather than relying exclusively on international treaty provisions to bring domestic entities under the purview of fair and equitable benefit‐sharing.